Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1152/jn.00341.2020
|View full text |Cite
|
Sign up to set email alerts
|

Balance perturbation-evoked cortical N1 responses are larger when stepping and not influenced by motor planning

Abstract: The cortical N1 response to balance perturbation is observed in electroencephalography recordings simultaneous to automatic balance-correcting muscle activity. We recently observed larger cortical N1s in individuals who had greater difficulty resisting compensatory steps, suggesting the N1 may be influenced by stepping or changes in response strategy. Here, we test whether the cortical N1 response is influenced by stepping (planned steps vs. feet-in-place) or prior planning (planned vs. unplanned steps). We hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(44 citation statements)
references
References 45 publications
1
41
0
Order By: Relevance
“…Ranking in order of importance for the four parameters when used together based on mean of |SHAP| value (average impact on model output, Red means higher values of the parameter had positive impact, blue means lower values of the parameter had positive impact). > TNSRE-2021-00342< compensatory balance responses following N1 peaks was in the range of 150 -200 ms, which agrees with the temporal course of involuntary or voluntary responses to the ongoing somatosensory inputs [17,53,54]. It should be noted that the magnitude of N1 evoked during our balance task where the exact time of perturbation is relatively small in comparison (around -2 µV versus -10 µV) to that elicited during the external perturbation task (see Fig.…”
Section: Discussionsupporting
confidence: 80%
“…Ranking in order of importance for the four parameters when used together based on mean of |SHAP| value (average impact on model output, Red means higher values of the parameter had positive impact, blue means lower values of the parameter had positive impact). > TNSRE-2021-00342< compensatory balance responses following N1 peaks was in the range of 150 -200 ms, which agrees with the temporal course of involuntary or voluntary responses to the ongoing somatosensory inputs [17,53,54]. It should be noted that the magnitude of N1 evoked during our balance task where the exact time of perturbation is relatively small in comparison (around -2 µV versus -10 µV) to that elicited during the external perturbation task (see Fig.…”
Section: Discussionsupporting
confidence: 80%
“…Further, habituation of agonist-antagonist cocontraction with practice in high threat conditions is associated with habituation of the emotional response ( Zaback et al, 2019 ), which may be easier to modify than the abnormal involuntary behavior observed at more severe stages of balance impairment ( McKay et al, 2021 ). We previously suggested that the cortical N1 could reflect compensatory cortical control based on larger amplitudes in young adults with lower balance ability ( Payne and Ting, 2020b ) and on trials with compensatory steps ( Payne and Ting, 2020a ). This non-specific cocontraction could be another way in which compensatory cortical control is engaged.…”
Section: Discussionmentioning
confidence: 99%
“…A cortical response, termed the “N1” for the first negative peak in the evoked electroencephalography signal, occurs in the supplementary motor area ∼150 ms after a balance disturbance ( Marlin et al, 2014 ; Mierau et al, 2015 ). We have previously suggested that the cortical N1 may reflect compensatory cortical engagement in balance recovery because it is enhanced in young adults with lower balance ability ( Payne and Ting, 2020b ) and on trials in which compensatory steps are taken ( Payne and Ting, 2020a ). The cortical N1 is also influenced by cognitive processes including attention ( Quant et al, 2004 ; Little and Woollacott, 2015 ), perceived threat ( Adkin et al, 2008 ; Mochizuki et al, 2010 ), and predictability ( Adkin et al, 2006 , 2008 ; Mochizuki et al, 2008 , 2010 ) and may therefore reflect cognitive-motor interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Further, habituation of agonist-antagonist cocontraction with practice in high threat conditions is associated with habituation of the emotional response (Zaback et al, 2019), which may be easier to modify than the abnormal involuntary behavior observed at more severe stages of balance impairment (McKay et al, 2021). We previously suggested that the cortical N1 could reflect compensatory cortical control based on larger amplitudes in young adults with lower balance ability (Payne and Ting, 2020a) and on trials with compensatory steps (Payne and Ting, 2020c). This nonspecific cocontraction could be another way in which compensatory cortical control is engaged.…”
Section: Discussionmentioning
confidence: 99%
“…A cortical response, termed the "N1" for the first negative peak in the evoked electroencephalography signal, occurs in the supplementary motor area ~150 ms after a balance disturbance (Marlin et al, 2014;Mierau et al, 2015). We have previously suggested that the cortical N1 may reflect compensatory cortical engagement in balance recovery because it is enhanced in young adults with lower balance ability (Payne and Ting, 2020a) and on trials in which compensatory steps are taken (Payne and Ting, 2020c). The cortical N1 is also influenced by cognitive processes including attention (Quant et al, 2004b;Little and Woollacott, 2015), perceived threat (Adkin et al, 2008;Mochizuki et al, 2010), and predictability (Adkin et al, 2006;Adkin et al, 2008;Mochizuki et al, 2008;Mochizuki et al, 2010) and may therefore reflect cognitive-motor interactions.…”
Section: Introductionmentioning
confidence: 99%